Let’s dive into petrochemical industry / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2021)
The main agenda of his session included the upstream and downstream business in oil and gas industry; the relationship between pe-troleum, petrochemicals and polymers, and petrochemicals building blocks related to petroleum-based polymers (plastics). Petro-chemical means the chemical products that can be obtained from fossil fuels such as pe-troleum, coal, natural gas, or non-renewable sources. Dr Mohammad Azizol bin Abdul Wa-hab also explained about the importance of petrochemicals, petrochemical-based prod-ucts and activities in petroleum business seg-ments: upstream (exploration, drilling and production), midstream (processing, pre-process, storage and transmission), and downstream (oil refining, convert to energy or petrochem-icals products mainly from two classifications: polymers and chemicals, lubricants, and fer-tilisers). Apart from that, he gave a speech about the growth of petrochemical in Saudi Arabia, in which he accentuated the typical composition of crude oil and its refining process until it can yield the petrochemical-based consumer goods.